THEORETICAL APPROACHES TO THE LIBERALIZATION OF FOREIGN TRADE - Zhang, Meng (International Conference on Business & Management, 2025)
The liberalization of foreign trade represents a cornerstone of modern economic integration and development strategies. This article provides an in-depth theoretical analysis of the principal economic approaches to trade liberalization within the IMRAD framework. Classical, neoclassical, new trade, endogenous growth, and institutional theories are systematically reviewed and compared. The study highlights both static and dynamic gains from trade liberalization, as well as structural constraints and distributional effects. By synthesizing multiple theoretical perspectives, the article offers a comprehensive conceptual foundation for master’s-level research and future empirical investigations.